Hand nerve function after mountain bike cycling - Fardelin , G.; Ricklund, N.; Bryngelsson , I.L. (Journal of Science and Cycling, 2022)
Hand-arm vibrations can cause permanent injuries and temporary changes affecting the sensory and circulatory systems in the hands. Vibrational effects have been thoroughly studied within the occupational context concerning work with handheld vibrating tools. Less is known about vibrational exposure and risk of effects during cycling. In the present study, 10 cyclists were recruited for exposure measurements of hand-arm vibrations during mountain bike cycling on the trail, and the effects on the nerve function were examined with quantitative sensory testing (QST) before and after the ride.